Trumpeter Swan Cygnus buccinator range expansion programs in the northern Rocky Mountains, USA - Shea, Ruth; Lockman, Dave C; Mitchell, Carl D (Wildfowl, 2013)
We review the status of Trumpeter Swans in the northern Rocky Mountains of the United States.Â Limited winter habitat appears to be inhibiting population growth. To alleviate problems of overcrowding,Â and to meet long-term population goals, experiments in range expansion proceduresÂ began in 1986. Overall, relocated Trumpeter Swans have survived well and acted as decoys forÂ other swans. We discuss the use of various age classes and release methods.